Outcomes of adult T-Cell leukemia/lymphoma with allogeneic stem cell transplantation: single-institution experience. Issue 9 (29th July 2021) - Epstein-Peterson, Zachary D.; Ganesan, Nivetha; Barker, Juliet N.; Drullinsky, Pamela R.; Ghione, Paola; Jakubowski, Ann A.; Kumar, Anita; Moskowitz, Alison J.; Noy, Ariela; Perales, Miguel-Angel; Ponce, Doris M.; Schoder, Heiko; et al.
Abstract: Few publications exist concerning allogeneic hematopoietic cell transplant (alloHCT) outcomes in non-Japanese patients with HTLV-1-associated ATLL. We detail the patient and disease characteristics, transplant approach, and clinical outcomes in 17 patients with ATLL at our institution who underwent alloHCT. We report favorable outcomes, with 8/17 in ongoing remission, 2/17 with prolonged (>6 years) disease-free survival, and a low incidence of transplant-related mortality (2/17). These results validate the feasibility and efficacy of alloHCT in non-Japanese patients with ATLL.